Observation of Sort, Set, Shine, Standardize, and Sustain in a Manufacturing Company Surabaya - Muhammad Aji Satria; Meirina Ernawati; Bagus Wicaksono; Sahrir Sillehu (Universitas Airlangga, 2022)
Introduction: The implementation of the Occupational Health and Safety system in industry aims to create a workplace that is safe, healthy, and free from environmental pollution so that it minimizes the probability of occupational accidents and illness. The arrangement of goods and comfortable work environment can affect labour productivity. Creating an orderly and comfortable working environment can be manifested in a good Sort, Set, Shine, Standardize (5S) application. The purpose of this study is to describe the implementation of the 5S program in PT Albea Rigid and Packaging Surabaya. Method: This research was a descriptive qualitative research. The data used in this study were secondary data which were obtained from the EHS Department of PT. Albea Rigid Packaging Surabaya which were later analyzed using several theoretical references. Variables in this research were observation of Sort, observation of Set, observation of Shine, observation of Standardize and observation of Sustain. The analyzed data were further interpreted and presented in a narrative form. Results: The results show that the implementation of 5S in the Injection Molding Production area of PT. Albea Rigid Packaging Surabaya, before the socialization, had a score of 16 points and after the socialization it increased to 40 points. Even though the score has increased, the implementation of the 5S was still not running optimally. Conclusion: The principle of Standardize still had the same score before and after the socialization, while for the other 3 principles, namely Sort, Set and Shine, there was an increase in points after the socialization.